2019
DOI: 10.1103/physrevb.100.075149
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio simulations of x-ray emission spectroscopy with the GW+ Bethe-Salpeter equation method

Abstract: In order to calculate x-ray emission spectroscopy (XES) spectra, we apply the GW + Bethe-Salpeter equation (GW + BSE) method on a basis of extended quasiparticle theory which enables one to treat an arbitrary excited state as an initial state, because the initial state in the XES process is a highly excited state with a core hole. Compared to the preexisting experimental data of XES fluorescence photon energy, the calculated GW + BSE results give values with about 1-eV accuracy, which is comparable to the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 61 publications
(76 reference statements)
0
18
2
Order By: Relevance
“…Our analysis presented in this Letter demonstrates that those studies cannot have found the QP solution because their spectral function would look like the yellow spectrum in Figure c. Linearizing the QP equation by a Taylor expansion to first-order around ε n , as done for such a spectral function in refs , , and , leads to uncontrollable results, which partly explains the large deviation of the reported results from experiment. , Furthermore, the linearization error rapidly increases with increasing BE and may already amount to 0.5 eV for deeper valence states, as shown in ref . As already pointed out in our previous work, eq should always be solved iteratively for core states.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Our analysis presented in this Letter demonstrates that those studies cannot have found the QP solution because their spectral function would look like the yellow spectrum in Figure c. Linearizing the QP equation by a Taylor expansion to first-order around ε n , as done for such a spectral function in refs , , and , leads to uncontrollable results, which partly explains the large deviation of the reported results from experiment. , Furthermore, the linearization error rapidly increases with increasing BE and may already amount to 0.5 eV for deeper valence states, as shown in ref . As already pointed out in our previous work, eq should always be solved iteratively for core states.…”
mentioning
confidence: 69%
“…Previous GW core-level studies for small molecules 31 , 41 reported G 0 W 0 calculations performed on top of generalized gradient approximation (GGA) or hybrid functionals with a low amount of exact exchange. Our analysis presented in this Letter demonstrates that those studies cannot have found the QP solution because their spectral function would look like the yellow spectrum in Figure 1 c. Linearizing the QP equation by a Taylor expansion to first-order around ε n , as done for such a spectral function in refs ( 31 ), ( 41 ), and ( 63 ), leads to uncontrollable results, which partly explains the large deviation of the reported results from experiment. 31 , 41 Furthermore, the linearization error rapidly increases with increasing BE and may already amount to 0.5 eV for deeper valence states, as shown in ref ( 33 ).…”
mentioning
confidence: 79%
“…The most popular methods for computing core electron properties for molecules can be divided into two main categories: delta-SCF-like methods, and the closely related linear response (LR) and equation-of-motion (EOM) methods. Green’s function methods, which are closely related to LR methods, have been used for materials in connection with DFT methods. …”
Section: Introductionmentioning
confidence: 99%
“…Recent work has been done using the BSE to calculate emission by considering large systems with a single core-hole as the initial state, i.e., a defect calculation, and then calculating the BSE response of creating an excited electron in the core level and valence hole. 45 2.3.5 Resonant inelastic X-ray scattering. Valence resonant inelastic X-ray scattering (RIXS) is an increasingly widely used technique for probing low-energy excitations in a system using X-ray in/X-ray out spectroscopy.…”
Section: Haydock Recursionmentioning
confidence: 99%